2017
DOI: 10.1111/jocn.13590
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review on women living with obstetric fistula and after treatment experiences

Abstract: The review provides insights into avenues of improving care provision and delivery by health professionals and policy makers. It also exposes areas that need further research for quality care provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Fistula formation occurred for nine women during the first delivery, while for six women, it was between the second to fifth deliveries. Hence, women were from all the reproductive life stages and so concurred with earlier studies (Degge, Hayter, & Laurenson, 2017;Heller & Hannig, 2017). This supports the arguments that, since it happens to both younger and older women of any parity, lack of access to SBA and Emergency Obstetric Care (EmOC) appears to be the primary cause (Abrams, 2012;Bangser et al, 2011;Heller & Hannig, 2017;Phillips et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…Fistula formation occurred for nine women during the first delivery, while for six women, it was between the second to fifth deliveries. Hence, women were from all the reproductive life stages and so concurred with earlier studies (Degge, Hayter, & Laurenson, 2017;Heller & Hannig, 2017). This supports the arguments that, since it happens to both younger and older women of any parity, lack of access to SBA and Emergency Obstetric Care (EmOC) appears to be the primary cause (Abrams, 2012;Bangser et al, 2011;Heller & Hannig, 2017;Phillips et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…This isolation and denial from most spheres of their social agency marked their perception that this disease was unique to them, which further refrained them from persuasively searching for a solution. The study captured a polarised situation in regard to the relationships with partners, relatives and community in general, as many women with fistula expressed that they received support from husbands and relatives and that their condition did not necessarily lead to divorce or separation, contrary to findings observed in other studies [4,13,[24][25][26][27]. Nonetheless, this finding should be interpreted with caution, as a remarkable number of women with fistula were registered as unmarried, proving that it is not possible to ascertain a possible connection between the onset of fistula and marital status, while understanding that the definition of marital status in rural settings in Mozambique is challenging.…”
Section: Discussionmentioning
confidence: 87%
“…Child loss, which was almost an inevitable aftermath for the vast majority of women with fistula, further increased these women's sorrow and sense of failure from fulfilling their woman's role of motherhood [14]. Women's grief, much present during the interviews, calls for the need for post-repair psychosocial support [13,24]. Paradoxically, they expressed reliance on some family support, albeit limited just to the treatment seeking process, leaving other aspects of psychological and social support, affection and comfort, uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…2931 To our knowledge, although patients are often encouraged to return for a follow­up visit, most services provided by fistula treatment programmes are limited to hospital stay, including sexual and reproductive health counselling at discharge, psychological counselling, skill empowerment, literacy classes, or support groups before discharge. 14,15,20,32 A rethink of fistula programming to include locally adapted follow­up mechanisms to prevent post­repair recurrence is needed to safeguard the health of women after fistula repair. 29…”
Section: Discussionmentioning
confidence: 99%
“…10,11,18,19 Similarly, data for fertility or pregnancy and childbirth after successful fistula repair are scarce, especially from robust studies that are able to provide a precise estimate of pregnancy and delivery outcomes. 10,14,18,2022 A review 23 in sub­Saharan Africa found that the risk of adverse maternal and neonatal health outcomes was elevated in women after fistula surgery, and that post­surgical fistula recurrence was the most common maternal complication, occurring in 5% of deliveries. 23 Although the general recommendation to women after fistula repair is to seek care at health­care facilities and deliver via scheduled caesarean section for any post­repair pregnancies, 13,21,22 the proportion of women delivering via elective caesarean section is low (45%).…”
Section: Introductionmentioning
confidence: 99%